L’Eclipsi, de Georges Perec - Adrià Pujol Cruells (Catalonia)
After six years of work, the Catalan version of La Disparition comes to light, with the title L’Eclipsi. The legacy of Georges Perec grows, crosses borders and times and, on this occasion, also contributes to enlarging Catalan literature.